Operation analysis and parameter optimization of the conveying device for uniform crushed straw throwing and seed-sowing machines - Gu, Fengwei; Zhao, Youqun; Hu, Zhichao; Shi, Lili; Wu, Feng; Xu, Hongbo; Gao, Xuemei (International Journal of Agricultural and Biological Engineering, 2024)
Uniform crushed straw throwing and seed-sowing machines can achieve the processes of straw chopping, straw transport, sowing, fertilization, and straw mulching at the same time, which is widely used in many areas of China. Conveying device is one of the important components used to convey, elevate and throw straw. However, the problems of high power consumption and congestion affect the promotion of the machine. Therefore, the conveying device of uniform crushed straw throwing and seed-sowing machine was analyzed in order to determine its device operation mechanism. Kinematic and dynamic analyses of particles of crushed rice straw during lifting and dispersion are used to develop a flexible-body model of rod-shaped and agglomerate-shaped crushed straw and a coupling model including the mechanical structure of the device. By integrating computational fluid dynamics and the discrete element method, the gas-solid coupling theory in numerical simulations and motion analysis of crushed straw particles is used to determine how the flow field and motion characteristics affect the conveying performance. Besides, regression equations to describe the relationships between the factors and each assessment index were established by using the regression analysis and response surface analysis with the software Design-Expert. The effect of throwing blade speed X1, conveying volume of crushed straw X2, and pipeline diameter X3 on the throwing speed of crushed straw Y1 and specific power consumption Y2 were investigated. The highest throwing speed of crushed straw and lowest specific power consumption are the optimization goal .The results of optimization showed that the predict the best optimal parameters were 2000 r/min throwing blade rotational speed, 1.4 kg/s conveying volume, and 220 mm pipeline diameter, the planter achieved a throwing speed of 12.2 m/s and specific power consumption of 9179 m2/s2. And then a field test verification was conducted. The planter achieved a throwing speed 12.4 m/s and specific power consumption 9070 m2/s2 while selecting the best optimal parameters. Thus, the optimal parameters can provide a high-performance operation and satisfy the actual operation requirements The results provide a theoretical basis and data support for seeding technology innovation and equipment optimization to ensure uniform crushed straw throwing in dense rice stubble fields. Keywords: rice straw stubble, uniform crushed straw throwing, coupled CFD-DEM, response surface analysis DOI: 10.25165/j.ijabe.20231606.7057 Citation: Gu F W, Zhao Y Q, Hu Z C, Shi L L, Wu F, Xu H B, et al. Operation analysis and parameter optimization of the conveying device for uniform crushed straw throwing and seed-sowing machines. Int J Agric & Biol Eng, 2023; 16(6): 28–36.